Analysis of Job Satisfaction and Professional Academic Performance of Graduates in Psychology from a University in Ecuador - Guido Leonel Rosales-Jaramillo; Andrea Yesenia Rodal-Genovez; Viviana Tatiana Chumbi-Toledo; Román Mauricio Buñay-Andrade (Universidad Nacional, Costa Rica, 2017)
Studies conducted in higher education institutions provide important information about professional performance. The present study had as objective to determine the level of job satisfaction, and establish correlation between this construct and extrinsic factors that can intervene in this job satisfaction. This is a descriptive, correlational, probabilistic, and non-experimental work. There is a population of 1207 professionals and the calculated sample was of 307. Theoretical and empirical methods were implemented, such as analysis, synthesis, historical-logical method, literature review, survey, and for the statistical processing, the Chi-squared test was used to cross qualitative variables. It was concluded that there is a strong correlation between the dependent variable and the variables of salary, positions held, and employment sectors. The relation between satisfaction and academic performance is weak. It is recommended to conduct a study with a more extended sample, with the integrator model of satisfaction, and to develop strategies from the pregraduate training to contribute to keep high levels of satisfaction in professional graduates in psychology.